Kasus Perdata Dan Pidana Pada Perselisihan Merek Dagang Studi Kasus Ayam Geprek Bensu - Judika Christian Manalu; Lutvia Nazwa Tambunan; Rini Pardilla; Suci Rahma Stefani (Jurnal Ilmu Ekonomi dan Bisnis, 2026)
This research analyzes the trademark dispute between "Geprek Bensu" (Ruben Onsu) and "I Am Geprek Bensu" (PT Ayam Geprek Benny Sujono), a significant case in Indonesian trademark law practice. The study employed a normative juridical method combined with a case study approach, drawing upon the Law No. 20 of 2016 concerning Marks and Geographical Indications and the relevant rulings from the Central Jakarta Commercial Court and the Supreme Court. The primary objective was to analyze both the civil and criminal aspects of the trademark conflict. The analysis revealed that the court dismissed Ruben Onsu's lawsuit because PT Ayam Geprek Benny Sujono was proven to be the first party to register the mark (the first-to-file principle). The study concludes that trademark registration is the key to legal protection. Furthermore, resolving trademark disputes through the civil court track is more effective for ensuring legal certainty, while also stressing the critical importance of good faith in maintaining fair business competition